2005
DOI: 10.1017/s0265021505000220
|View full text |Cite
|
Sign up to set email alerts
|

The ProSeal™ Laryngeal Mask Airway and the Laryngeal Tube Suction™ for ventilation in gynaecological patients undergoing laparoscopic surgery *

Abstract: Both devices provide a secure airway even under conditions of elevated intra-abdominal pressure. In this pilot study, no differences concerning handling or quality of airway seal were detected between PLMA and LTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 19 publications
3
24
0
4
Order By: Relevance
“…12 However, some studies have suggested that supraglottic airway devices may be safely used during laparoscopic surgery, despite the increased risk of aspiration due to elevated intraabdominal pressure (typically limited to 15 mm Hg). 13,14 Our study suggests that the Combitube provides better airway protection than the Classic LMA. Some clinical studies have not demonstrated this, 15 although studies in prehospital use suggest that the Combitube provides better protection against aspiration than the Classic LMA.…”
Section: Discussionmentioning
confidence: 75%
“…12 However, some studies have suggested that supraglottic airway devices may be safely used during laparoscopic surgery, despite the increased risk of aspiration due to elevated intraabdominal pressure (typically limited to 15 mm Hg). 13,14 Our study suggests that the Combitube provides better airway protection than the Classic LMA. Some clinical studies have not demonstrated this, 15 although studies in prehospital use suggest that the Combitube provides better protection against aspiration than the Classic LMA.…”
Section: Discussionmentioning
confidence: 75%
“…There are 9 randomized trials comparing PLMA with various other airway devices in laparoscopic gynaecological surgery. This includes comparison with ETT (4) and one each with SLMA, i-gel, LTS and Cobra PLA and one comparing PLMA, SLMA and i-gel [48][49][50][51][52][53][54][55]62]. The PLMA had equivalent functionality with ETT.…”
Section: Sad In Gynaecological Laparoscopymentioning
confidence: 99%
“…Roth and colleagues compared PLMA and LTS for ventilation in gynecological patients. They concluded both devices provide a secure airway even under conditions of elevated intra-abdominal pressure 18 . Our study demonstrates that the LTS is a useful device for management of airway in laparoscopic cholecystectomy and the clinical performance of the disposable and the reusable LTS are similar with regard to oxygenation and ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of the supraglottic airway devices, few studies compared these different tools for airway management in laparoscopic procedures [16][17][18] . One study concluded that Proseal Laryngeal Mask Airway (PLMA) is a reasonable alternative to conventional tracheal tube for gynecological laparoscopy with same advantages 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation